Digging Companies Crucial Aspect Measurement: Risk Maturity Level, Assessment of XYZ Bank - Vincentia; Kurnia Fajar Afgani; Marziana Marzuki (Integrasi Sains Media, 2023)
Risk management is an important aspect to be owned by companies and measured through risk maturity level to utilize opportunity and minimize losses in processes with uncertainty or potential for two or more possibilities to happen. This research aims to measure one of the banking state-owned corporations' risk maturity levels to measure implementation, readiness, and maturity, and application of risk management according to Indonesia’s regulations from Otoritas Jasa Keuangan, Kementerian BUMN, and Bank Indonesia regarding risk management in the banking industry. The main framework used is risk maturity level from ISO 31000:2018, with five indicating levels: initial, managed, defined, quantitatively managed, and optimized. This study uses a mixed method in data collection. Primary data will be collected quantitatively through questionnaires for the company employees, and qualitatively through interviews with related divisions, which in this research is the Enterprise Risk Management Division and divisions which are working in the risk management implementation process. While the secondary data will be collected through documents related to risk management processes. All data will be measured through weighting and Analytical Hierarchy Method. To get the company’s risk maturity level, criteria from each level according to ISO 31000:2018 must be fulfilled. As a company in a high-regulated industry and high-risk level due to the trust-based business model and its impact to internal and external parties, the company is expected to have a high level of risk maturity level, which is in level four (quantitatively managed) or level five (optimized). The expected findings from this study are improvements and suggestions for companies who want to increase or maintain their maturity level, and for the next researchers.